As condicionalidades do Banco Interamericano de desenvolvimento e as políticas de educação profissional no Brasil - Abrantes, Terezinha dos Anjos (2019)
This work analyzes the economic and political conditionality of Inter-American Development Bank (IDB) for the Brazilian professional education. The main objective is to identify the education policies entailments in Brazil based on the IDB and how these orientations or conditionalities influence to the country professional education from 1988 to 2018. This analysis covers since the historical context of IDB birth and expansion as the market and capital tool to the professional training proposed for former students of Federal Institutes (FIs), of National Program of Technical Education and Employment Access (PRONATEC) and of secondary school after the determined reform by Law 13.415/2017 under the economic development premises, the qualification for work and the employability.The research and the official documents published on the Bank and governmental web sites, show that the IDB both promoted the borrower countries debt with unfairly high interest policy and influenced the Brazilian educational principles through the dispensed determinations in the financing project and the certain orientations by technical advisory. And, after the Bank conditionalities were accepted, the Brazilian professional education began to serve the market interests forming a reservation force and cheapening the labor cost among other consequences.The research work notices the IDB and other multilateral financial institutions consider the education responsible for the borrower countries economic failure, as though it guided the economy. But, during 58 years of its existence, the total amount of financing projects for education in Brazil do not reach 10% of the national budget for 2018 which is minimal. Other research result is the verification that both PRONATEC and the mentioned reform of Secondary school, in fact, serve only to qualify labor for the productive sector demands, according to employability, yet, without worrying about the education offer for the human formation. Finally, it was verified the FIs, although in some aspects, they are similar to the American Superior Technical Institutes (STI), in general, they show major differences, the greatest one is the fact that the FIs offer free public education and the STIs charge annuity rates.